2022
DOI: 10.4236/ojce.2022.123021
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical Characterization of Termite Mound Soils of Congo

Abstract: This study is to determine the activities and correlations in the fundamental properties of the termite mounds soils Cubitermes spp and Macrotermes sp.The Intrinsic properties depend on the mineralogy, organic composition and texture of soil. Grain size, Atterberg limits and soil blue values are geotechnical properties that were used to characterize the two soils. On the basis of the geotechnical properties, specific surface area, cation exchange capacity, relative activity, surface activity and soil activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…From Figure 7, Figure 8, Figure 10 and Table 2, the evolution of the plasticity index as a function of the specific surface area of twelve soils containing all minerals (kaolinite and illite), is a linear fit [6] [7] [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From Figure 7, Figure 8, Figure 10 and Table 2, the evolution of the plasticity index as a function of the specific surface area of twelve soils containing all minerals (kaolinite and illite), is a linear fit [6] [7] [19].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the blue value of a soil is closely related to the cation exchange capacity and the specific surface. Indeed, it has been shown that the specific surface as a function of the cation exchange capacity forms a linear fit [6] [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil blue value characterizes the activity of the clay fines in lateritic gravelly soils and reflects surface activity [18]. The specific surface depends on the mineralogy, organic composition and texture of lateritic gravelly soils [14,[24][25][26].…”
Section: Figure 5 Correlation Between Plasticity Index and Blue Value...mentioning
confidence: 99%
“…Ac activity characterizes the mineral contained in the fine clay of lateritic gravels. When the clay content is high enough, grains larger than two micrometers are embedded in the clay and hardly touch each other [24][25][26]. In Figure 7, Ac -are the directing coefficients of the straight lines delimiting the areas of activity of the clay fraction of lateritic gravels (inactive, normal and active).…”
Section: Figure 7 Activity Of Lateritic Gravelsmentioning
confidence: 99%